Numerical Simulation of Empty-Hole Effect during Parallel-Hole Cutting under Different In Situ Stress Conditions - Zhengyu Wu; Dayou Luo; Feng Chen; Wulin Huang (Advances in Civil Engineering)
With the progress of deep mining in mine exploitation, the effect of the in situ stress field plays a more and more significant and crucial role in rock blasting. To uncover the impact of in situ stress field on empty-hole effect during parallel-hole cutting, the distribution and the trend of changes in dynamic stress around empty hole during blasting under different in situ stress conditions are simulated based on the basic model for parallel-hole cutting using 3D finite element analysis software ANSYS/LS-DYNA and implicit-explicit analysis method. Subsequently, the law of variation in the empty-hole effect under different in situ stress conditions is determined, and the effects of horizontal and vertical stress fields are analyzed in detail. The simulation results show that the overall increase in in situ stress can facilitate compressive failure and inhibit tensile failure in the rock mass around an empty hole during blasting. When empty holes are arranged horizontally, the effect of the vertical stress field is consistent with that of the in situ stress field, while the effect of the horizontal stress field is opposite to that of the in situ stress field. With the increased stress, the inhibitive effect of the vertical stress field on tensile stress around an empty hole is remarkably stronger than that of the horizontal stress field. Finally, the numerically simulated results are verified by the theoretical calculation. This study can provide new insight and a simple but accurate numerical simulation method to investigate how the in situ stress field affects the empty-hole effect, especially in deep mining.